2018
DOI: 10.1017/s0305000918000168
|View full text |Cite
|
Sign up to set email alerts
|

Caused motion across child languages: a comparison of English, German, and French

Abstract: Previous research on motion expression indicates that typological properties influence how speakers select and express information in discourse (Slobin, 2004; Talmy, 2000). The present study further addresses this question by examining the expression of caused motion by adults and children (three to ten years) in French (Verb-framed) vs. English and German (Satellite-framed). Participants narrated short animated cartoons showing an agent displacing objects and varying along several dimensions (Path, Manner). A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(52 citation statements)
references
References 34 publications
(57 reference statements)
2
43
0
1
Order By: Relevance
“…In summary, we found both similarities and differences in the way preschool-aged speakers of English and Greek described our motion events. Not surprisingly, older children in both language groups tended to provide more motion information than younger children did (see Henriks 2006 andHickmann et al 2018 for similar developmental findings in English-, German-, and French-speaking children). Both English-and Greek-speaking children mentioned Manner information more often than Path information (cf.…”
Section: Manner Pathmentioning
confidence: 84%
See 1 more Smart Citation
“…In summary, we found both similarities and differences in the way preschool-aged speakers of English and Greek described our motion events. Not surprisingly, older children in both language groups tended to provide more motion information than younger children did (see Henriks 2006 andHickmann et al 2018 for similar developmental findings in English-, German-, and French-speaking children). Both English-and Greek-speaking children mentioned Manner information more often than Path information (cf.…”
Section: Manner Pathmentioning
confidence: 84%
“…Papafragou et al 2002;2006; Papafragou & Selimis 2010a for a similar finding in older children). Even earlier effects of language environment on motion event description have been demonstrated in experimental studies comparing 3-year-old speakers of the verb-framed languages Turkish (Özçalişkan & Slobin 2000;Allen et al 2007;Özyürek et al 2008), French (Hickmann & Hendriks 2006;Hickmann et al 2009;Hickmann et al 2018) and German (Hickmann et al 2018) to agematched English speakers, as well as in studies comparing the spontaneous speech of 2-year-old Korean-and English-speaking children (Choi & Bowerman 1991). Crosslinguistic differences in the encoding of event components have been documented in the verb learning patterns of speakers as young as 3 years of age (Maguire et al 2010;Skordos & Papafragou 2014).…”
Section: Introductionmentioning
confidence: 97%
“…In this context, studies on the expression of motion events have often emphasized the influence of language-independent general cognitive factors, such as the increasing processing capacities of children, which in turn impact the length and complexity of utterances (Ochsenbauer and Engemann 2011). Along with this, increasing vocabulary and discourse becoming more organized are decisive (Hickmann et al 2018). This is also in line with the usage-based approach as it assumes that the constructional patterns gain in productivity and thus become gradually more complex and abstract through language acquisition (see Section 1.1).…”
Section: Discussionmentioning
confidence: 99%
“…The investigation of the verbalization of caused-motion events in monolingual and bilingual speakers has a long tradition. Using a framework by Talmy (1985), which cannot be further discussed here, studies have focused on the semantic contents of components expressed during the verbalization of motion events-more specifically, the verb and the directional phrase-in both monolinguals and bilinguals (Ochsenbauer and Engemann 2011;Hickmann et al 2018). Although idiosyncratic uses were not the focus of these studies, results in English-French and German-French children show that productions sometimes consist of structures that did not correspond to the monolingual use of language (Engemann 2013;Hickmann et al 2018).…”
Section: Motion Events and The Caused-motion Constructionmentioning
confidence: 99%
“…Our research findings are generally in line with the results from investigations of L2 linguistic encoding of motion events, particularly those involving an acquisition of advanced linguistic skills, such as syntactic organization and discourse strategy. To cite an example, Ji and Hohenstein (2014a, b) systematically investigate how English learners of Chinese syntactically package varied semantic components for complex caused motion events (e.g., Manner, Cause, Path, etc.). It is reported that even the advanced L2 learners have not fully acquired the typical syntactic pattern in motion description in the target language.…”
Section: Discussionmentioning
confidence: 99%